Analytic Data on the Mineral Constituents of Tamarix articulata Vahl. and its accompanying Soils at Churu, Rajasthan - Sharma, B.M. (Journal of Soil and Water Conservation, 2022)
Leaf analysis yields important information on the nutritional status of the plant. It represents the resultant of a number of factors that have influenced leaf composition. But in addition, if the environmental factors, the most important of which is the soil, is also analysed, a complete picture would emerge about the soil plant relationship. This paper is intended to present the analytic data for field plants and their associated soils at Churu, Rajasthan. It is in continuation with the earlier work done on two dominant plants of the area by the’author (Sharma, 1966 a, b). Tanzarix articul ata Vahl is popularly known as Tarash’. It is a tree reaching a height of 40 to 50 feet and grows faster in the arid tract.. Th.; tree is widely distributed in Afghanistan, Persia and Africa (Duthie, 1960). In India it is common in Punjab and Rajasthan but in the area under investigation all the trees are planted ones. This investigation was carried out in 1960-62 around Churu town in the Bikaner division of Rajasthan. There is a vast expanse of sand all around the town with accumulation; at many places leading to the formation of dunes. The climate of the area is characterized by drought and high temperature. The rainfall is scanty and irregular. It is mainly received during the monsoon months. Wind velocity is quite high during the summers and sand storms are a common feature of the area.